PERAN DAN KINERJA LEMBAGA EKONOMI MASYARAKAT SEJAHTERA DALAM USAHATANI KAKAO DI DESA TINETE KECAMATAN AERE KABUPATEN KOLAKA TIMUR - Winda Eka Putri; Anas Nikoyan; Rosmawaty Rosmawaty (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2023)
The Prosperous Community Economic Institution is an alternative to improving farmer institutions. The Prosperous Community Economic Institution is considered a gateway to synergize various programs and activities, build networks and commitments between villages, sub-districts and districts. The Prosperous Community Economic Institution is less active in carrying out activities or work programs engaged in cocoa plantations, such as partnerships with companies that do not work properly and do not last long. This study aims to determine: the role of prosperous community economic institutions in cocoa farming and the performance of prosperous community economic institutions in cocoa farming in Tinete Village, Aere District, Kolaka Timur Regency. This research was carried out in Tinete Village, Aere District, East Kolaka Regency which was carried out from June 2021 to August 2021 with a total of 24 informants. Data analysis in this study used qualitative analysis. The results of the study show: the role of the Prosperous Community Economic Institution in Tinete Village can be said to have a role which is marked by the role of the Prosperous Community Economic Institution, namely both as an information center, as a financing institution, both in providing production inputs, building cooperation and a fairly good marketing institution. Whereas the performance of the Prosperous Community Economic Institution in Tinete Village can be said to be good which is marked by the institution's performance in the productivity aspect of farmer institutions which shows good, in the aspect of the quality of service provided by the institution to its members good and satisfactory and from the aspect of responsibility of the existing Prosperous Community Economic Institution in Tinete Village are also appropriate or said to be good.